Copper nanoparticle anchored biguanidine-modified Zr-UiO-66 MOFs: a competent heterogeneous and reusable nanocatalyst in Buchwald–Hartwig and Ullmann type coupling reactions. Issue 36 (24th June 2021) - Veisi, Hojat; Neyestani, Narges; Pirhayati, Mozhgan; Ahany Kamangar, Sheida; Lotfi, Shahram; Tamoradi, Taiebeh; Karmakar, Bikash
Abstract : We have designed a functionalized metal–organic framework (MOF) of UiO topology as a support, with an extremely high surface area, adjustable pore sizes and stable crystalline coordination polymeric structure and implanted copper (Cu) nanoparticles thereon. Abstract : We have designed a functionalized metal–organic framework (MOF) of UiO topology as a support, with an extremely high surface area, adjustable pore sizes and stable crystalline coordination polymeric structure and implanted copper (Cu) nanoparticles thereon. The core three dimensional Zr-derived MOF (UiO-66-NH2 ) was modified with a biguanidine moiety following a covalent post-functionalization approach. The morphological and physicochemical features of the material were determined using analytical methods such as FT-IR, SEM, TEM, EDX, atomic mapping, XRD and ICP-OES. The SEM and XRD results justified the unaffected morphology of Zr-MOF after structural modifications. The as-synthesized UiO-66-biguanidine/Cu nanocomposite was catalytically explored in the aryl and heteroaryl Buchwald–Hartwig C–N and Ullmann type C–O cross coupling reactions with excellent yields. A library of biaryl amine and biaryl ethers was synthesized over the catalyst under mild and green conditions. Furthermore, the catalyst was isolated by centrifugation and recycled 11 times with no significant copper leaching or change in its activity.